Trace elements and antioxidant enzymes associated with oxidative stress in the pre-eclamptic/eclamptic mothers during fetal circulation - Negi, Reena; Pande, Deepti; Karki, Kanchan; Kumar, Ashok; Khanna, Ranjana S.; Khanna, Hari D. (Clinical nutrition (Edinburgh, Scotland), 2012)
Pre-eclampsia is associated with oxidative stress in the maternal circulation. The aim of the study was to access the oxidative stress status by quantification of byproducts generated during lipid peroxidation; deficient antioxidant activity and inadequate trace elements during oxidative damage in the umbilical cord blood of pre-eclamptic/eclamptic mothers and its effect on the fetal outcome. In a case control study umbilical cord blood samples were collected during delivery from cases of pre-eclamptic/eclamptic mothers and from normotensive (uncomplicated pregnancy) subjects as controls. Concentrations of malondialdehyde, trace elements (Zn, Cu, Se, Mg) and antioxidant enzymes (SOD, GPx) were determined. Decreased levels of Zinc (p < 0.001), Copper (p < 0.001), Selenium (p < 0.005), Magnesium (p < 0.05), Superoxide dismutase (p < 0.001), Glutathione Peroxidase (p < 0.001) and elevated levels of malondialdehyde (marker of lipid peroxidation) in the umbilical cord blood of pre-eclamptic and eclamptic pregnancies were observed. Positive correlation between Zn and SOD (Pearson r = 0.581, p < 0.001), Cu and SOD (Pearson r = 0.576, p < 0.001) and Se and GPx (Pearson r = 0.445, p < 0.005) was also observed. The reduced levels of trace elements associated with inadequate amount of antioxidant enzymes may be important contributing factor associated with oxidative stress leading to endothelial dysfunction in pre-eclamptic/eclamptic mothers.